Assessing metacognitive and help-seeking strategies in schizophrenia: design and psychometric validation of the Versailles Metacognitive Strategies Evaluation Questionnaire. (February 2020) - Brunet-Gouet, Eric; Urbach, Mathieu; Ramos, Veronica; Ehrminger, Mickael; Aouizerate, Bruno; Brunel, Lore; Capdevielle, Delphine; Chereau, Isabelle; Dubertret, Caroline; Dubreucq, Julien; Fond, Guillaume; Lançon, Christophe; et al.
Objectives: The aim of this study is to design a questionnaire, the Versailles Metacognitive Strategies Evaluation Questionnaire, for assessing the use of metacognitive and help-seeking strategies in three key-domains of impaired daily functioning in schizophrenia. To evaluate its psychometric properties (internal consistency, factor structure, convergent and divergent validity, and stability). Design: Development of a questionnaire and psychometric validation procedure in patients with schizophrenia compared with healthy controls. Stability over one year was assessed in the patient group. Setting: Schizophrenia Centers of Expertise (French FondaMental Network). Subjects: A total of 141 patients with schizophrenia, among whom 77 participated in the second evaluation; 97 healthy subjects. Main measures: The Versailles Metacognitive Strategies Evaluation Questionnaire, Positive and Negative Symptoms Scale, Personal and Social Performance Scale, Evaluation of Cognitive Processes involved in Disability in Schizophrenia Scale, Schizophrenia Quality of Life Questionnaire, and Stages of Recovery Instrument. Results: From the 36-items version, stepwise exploratory factor analysis (oblimin) produced a 25-items scale which had a 3-factors structure (hygiene concern, social relationships, and hygiene help-seeking). Cronbach's were respectively equal to 0.91, 0.82, and 0.78. One-year stability was good (intra-class correlation coefficient = 0.7). The three factors showed good convergent validity with measures of quality of life (rho = 0.34, P ⩽ 0.001). The first two factors correlated with recovery ( N = 34, rho = 0.53, P ⩽ 0.001). On the contrary, the factors exhibited divergent validity, with no significant correlation, with symptoms and cognitive and psychosocial functioning ( P > 0.05). Factor structure in healthy controls did not match with that of patients, all items but one were found significantly different among groups. Conclusion: The Versailles Metacognitive Strategies Evaluation Questionnaire provides a simple and valid means to assess metacognitive strategies in individuals with schizophrenia.